EchinoDB, an application for comparative transcriptomics of deeply-sampled clades of echinoderms. Issue 1 (December 2016) - Janies, Daniel; Witter, Zach; Linchangco, Gregorio; Foltz, David; Miller, Allison; Kerr, Alexander; Jay, Jeremy; Reid, Robert; Wray, Gregory
Abstract Background One of our goals for the echinoderm tree of life project (http://echinotol.org ) is to identify orthologs suitable for phylogenetic analysis from next-generation transcriptome data. The current dataset is the largest assembled for echinoderm phylogeny and transcriptomics. We used RNA-Seq to profile adult tissues from 42 echinoderm specimens from 24 orders and 37 families. In order to achieve sampling members of clades that span key evolutionary divergence, many of our exemplars were collected from deep and polar seas. Description A small fraction of the transcriptome data we produced is being used for phylogenetic reconstruction. Thus to make a larger dataset available to researchers with a wide variety of interests, we made a web-based application, EchinoDB (http://echinodb.uncc.edu ). EchinoDB is a repository of orthologous transcripts from echinoderms that is searchable via keywords and sequence similarity. Conclusions From transcripts we identified 749, 397 clusters of orthologous loci. We have developed the information technology to manage and search the loci their annotations with respect to the Sea Urchin (Strongylocentrotus purpuratus ) genome. Several users have already taken advantage of these data for spin-off projects in developmental biology, gene family studies, and neuroscience. We hope others will search EchinoDB to discover datasets relevant to a variety of additional questions in comparative biology.